Ginsenoside Rg5 allosterically interacts with P2RY12 and ameliorates deep venous thrombosis by counteracting neutrophil NETosis and inflammatory response - Chen, Ziyu; Wang, Gaorui; Xie, Xueqing; Liu, Heng; Liao, Jun; Shi, Hailian; Chen, Min; Lai, Shusheng; Wang, Zhengtao; Wu, Xiaojun (Frontiers in Immunology, 2022)
Abstract Background: Deep venous thrombosis (DVT) highly occurs in severe COVID-19 patients and probably accounted for their high mortality. DVT formation is a time-dependent inflammatory process in which NETosis plays an important role. However, whether ginsenoside Rg5 from species of Panax genus could alleviate DVT as well as its underlying mechanism has not been elucidated. Methods: The interaction between Rg5 and P2RY12 was studied by molecular docking, molecular dynamics, surface plasmon resonance (SPR) and molecular biology assays. The preventive effect of Rg5 on DVT was evaluated in inferior vena cava stasis-induced mice, and immunocytochemistry, Western blot and calcium flux assay were performed in neutrophils from bone marrow to explore the mechanism of Rg5 in NETosis via P2RY12. Results: Rg5 allosterically interacted with P2RY12, formed stable complex and antagonized its activity via residue E188 and R265. Rg5 ameliorated the formation of thrombus in DVT mice, accompanied by decreased release of IL-6, IL-1β and TNF-ɑ in plasma, and suppressed neutrophil infiltration and NETs release. In LPS and PAF induced neutrophils, Rg5 reduced inflammatory responses via inhibiting the activation of ERK/NF-κB signaling pathway, while decreased cellular Ca2+ concentration, thus reduced the activity and expression of PAD4 to prevent NETosis. The inhibitory effect on neutrophil activity was dependent on P2RY12. Conclusions: Rg5 could attenuate experimental DVT by counteracting NETosis and inflammatory response in neutrophils via P2RY12, which may pave the road for its clinical application in the prevention of DVT related disorders.